How to implement successful e-Government: Case study of Sultanate of Oman - Al Salmi, Muatasim; Mohtar, Shahimi; Hasnan, Norlena (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2017)
Every government is seeking to provide the best services to its country to achieve efficiency and accepted performance. This goal could be achieved by improving the service performance of the entire sectors in society. Revealing key questions of e-government implementation and planning factors that would affect the success of e-Government is the study priority goal. Hence, the purpose of this research is to investigate and explore the factors that drive the e-government implementation and adoption that would affect the government performance. Finally, a case study using a secondary data from UN data along with study outcomes with recommendations as guidance for e-government projects in Sultanate of Oman is illustrated.